Instability in Models Connected with Fluid Flows I - Bardos, C. (Springer, 2017)
The notions of stability and instability play a very important role in mathematical physics and, in particular, in mathematical models of fluids flows. This title covers topics devoted to mathematical aspects of the theory but some novel schemes used in applied mathematics are also presented.